2012
DOI: 10.1590/s0103-51502012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dual-task training on dynamic and static balance control of pre-frail elderly: a pilot study

Abstract: INTRODUCTION: This quasi-experimental study is justified by the need to determine the effects of an intervention strategy aimed at improving the static and dynamic balance in pre-frail elderly women. We hypothesized that dual-task training on a treadmill, compared to simple training on a treadmill,may promote statistical difference in postural control of this group. OBJECTIVES: This study aimed to verify the measures of postural control in a group of pre-frail elderly after a physical therapy intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
10
0
3
Order By: Relevance
“…Although the changes in the CoP based parameters, especially in the maximum CoP displacement in the ML direction and in the mean CoP velocity, across tasks were greater for the individuals with PD, the values of these parameters did not significantly differ from the ones presented by the controls. Some studies [28,29] have found that individuals with PD have greater standing balance difficulties in dual-task conditions because they need to assign resources previously recruited in order to compensate the deficits in postural control. However, considering that the participants in this study were in early to middle stages of the disease, it is arguable that they did not have the need to recruit significantly more attentional strategies to maintain the postural stability than the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although the changes in the CoP based parameters, especially in the maximum CoP displacement in the ML direction and in the mean CoP velocity, across tasks were greater for the individuals with PD, the values of these parameters did not significantly differ from the ones presented by the controls. Some studies [28,29] have found that individuals with PD have greater standing balance difficulties in dual-task conditions because they need to assign resources previously recruited in order to compensate the deficits in postural control. However, considering that the participants in this study were in early to middle stages of the disease, it is arguable that they did not have the need to recruit significantly more attentional strategies to maintain the postural stability than the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Gregory et al 29 held a 26-week group training with elders involving dual task activities, and at the end, they concluded that exercises combined with a dual task can improve gait performance. Targino et al 11 proposed an activity in which during four weeks, elders carried out a training that consisted of walking on the treadmill (simple task) and walking on the treadmill with visual stimuli (dual task), which showed improvement in static balance at the end.…”
Section: Discussionmentioning
confidence: 99%
“…Number of research to improve balance in order to prevent falls of the aged is growing, especially of the institutionalized ones, as this fact entails an autonomy damage for this population, making it more fragile 9,10 . Studies have been finding that using dual-task training results in a balance improvement in the older women of the community 11 . However, studies verifying effects of dual-task training in institutionalized elders have not been found so far.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that these exercises improve the function of individuals, especially regarding static balance. 12 On the other hand, most of the other studies have less dealt with investigating the effect of hybrid exercises on motor skills. It seems that identifying the effect of exercises, which mostly considers systems involved in the movement especially balance, remains understudied.…”
Section: Introductionmentioning
confidence: 99%